PERANAN SISTEM INFORMASI AKUNTANSI PENJUALAN KREDIT DALAM MENINGKATKAN EFEKTIVITAS PENGENDALIAN INTERN PENJUALAN KREDIT PADA PT KERTAS PADALARANG (PERSERO) - Karmana , Dedi (Majalah Bisnis & IPTEK, 2021)
The aim of this research is to know how credit sales accounting information system can be applied to PT Kertas Padalarang (Persero), to know how effectiveness of internal control of credit penjulan at PT Kertas Padaralang (Persero), and to know how far the role of accounting information system of credit sales in support effectiveness of internal control of credit sales at PT Kertas Padalarang (Persero). The result of research on PT Kertas Padalarang (Persero) by using Spearman Rank correlation analysis from twenty (20) respondent questionnaire source, correlation calculation (rs = 0.85) indicates strong role between credit sales accounting information system with effectiveness of internal control credit sales. Meanwhile, when viewed from the calculation coefficient of determination that is equal to 72% in accordance with the criteria role means that the variable accounting information system credit sales play a role against the effectiveness of internal control of credit sales, and 28% influenced by other factors not examined. The relevance of the two variables above can also be seen from the significance of the relationship ie thitung = 6.934, greater than ttable = 2.399 which means H0 is rejected and H1 accepted means that the influence between X variable (credit sales accounting information system) and variable Y (effectiveness internal control of credit sales). From the result of hypothesis testing by using Rank Spearman analysis can be concluded that "credit sales accounting information system implemented has a big role in supporting effectiveness of internal control of credit sales". Keywords: accounting information system, credits, internal control.